869 Loss to Follow-Up for Radiation Treatment After Resection of Metastatic Brain Tumors: Analysis of a Non-Irradiated Cohort from a Private Insurance Database. (April 2023) - Haider, Ghani; Amoah Dadey, David Yaw; Rodrigues, Adrian; Pollom, Erqi; Adler, John R.; Veeravagu, Anand
Abstract : INTRODUCTION: Radiation treatment to the surgical bed of resected brain metastases is considered the standard of care due to its advantages in improving local and distant disease control. Overtime, SRS has replaced WBRT as the preferred modality due to preservation of long-term neuro-cognition. Despite this data and growing adoption, socio-economic disparities in clinical access, treatment and outcomes have been reported in minority groups, especially in oncologic patients – leading to sub-standard care for some patient populations. METHODS: Our sample was obtained from Optum Commercial Claims and Encounters Database and included all patients from 2004 to 2021 who did not receive SRS or WBRT within sixty days after resection of tumors metastatic to the brain. Regression analysis was done to identify factors responsible for loss to adjuvant radiation treatment. RESULTS: A total of 8, 362 patinets were identified who had undergone craniotomy for resection of metastatic brain tumors, of which 3, 430 (41%) patients did not receive any radiation treatment. Lung cancer, breast cancer, melanoma and colon cancer were the most common sites of primary tumor. Compared to patients who did receive some form of radiation treatment (SRS or WRBT), patients who did not get any form of radiation were more likely to be older (P = 0.0189), and non-white (P = 0.008). Patients with Elixhauser Comorbidity Index ≥3 were less likely to receive radiation treatment (P < 0.01). Fewer patients with household income ≥ $75, 000 did not receive radiation treatment (P < 0.01). CONCLUSIONS: Age, race, household income and comorbidity status were associated with differential likelihood to receive radiation treatment. This highlights the need for additional investigation of socio-economic determinants of radiation treatment delivery.